2019
DOI: 10.1093/neuonc/noz209
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between modifiable exposures and glioma risk: A Mendelian randomisation analysis

Abstract: Background The etiological basis of glioma is poorly understood. We have used genetic markers in a Mendelian Randomisation (MR) framework to examine if lifestyle, cardiometabolic and inflammatory factors influence the risk of glioma. This methodology reduces bias from confounding and is not affected by reverse causation. Methods We identified genetic instruments for 37 potentially modifiable risk factors and evaluated their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…While obesity is a well-known risk factor for the development of various types of cancer [7,8], conflicting results have been reported concerning the relationship between obesity and the risk of glioma in prospective cohort studies, case-control studies, and metaanalyses [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, a recent biological study suggested that adipocyte-released factors can promote the growth and progression of glioma cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…While obesity is a well-known risk factor for the development of various types of cancer [7,8], conflicting results have been reported concerning the relationship between obesity and the risk of glioma in prospective cohort studies, case-control studies, and metaanalyses [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, a recent biological study suggested that adipocyte-released factors can promote the growth and progression of glioma cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several cohort studies, case-control studies, and meta-analyses have evaluated the associations between adiposity and gliomas; however, the results from these studies have been inconclusive. While the majority of these studies have reported null associations [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], three studies reported positive associations [14,18,22]; one meta-analysis study found that there was a significant association between adiposity and glioma development in females [14], while one cohort study and one case-control study found that elevated BMI in early adulthood was significantly associated with increased risk of gliomas [18,22]. These…”
Section: Discussionmentioning
confidence: 96%
“…In addition, we found a stronger association between abdominal obesity and the risk of glioma development than BMI and the risk of glioma development. Our study included a large number of glioma cases (n=4,771) and is the second largest study to evaluate the association between obesity and glioma risk [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 After finding no strong associations, we subsequently investigated a more comprehensive list of dietary and lifestyle factors that commonly influence the risk of other cancers, again finding no evidence for strong associations. 17 Other researchers have used MR to examine the relationship between glioma and other traits with more success, purporting a strong association with leukocyte telomere length. 18,19 All of these MR analyses have, however, been predicated on assumptions about disease aetiology.…”
Section: Introductionmentioning
confidence: 99%